(untitled) (Journal of Hama University, 2021)
This study aims to: Identify the levels of burnout among the teachers of deaf children in the special education for deaf students institute in Damascus and its relation to the variants (Academic levels, Years of experience), The sample of the study consisted of 42 female teachers in the special education for deaf students’ institute. To achieve the goals of the study, the researcher used Maslache scale for burnout levels. The study showed the following results: 1- The special education teachers of deaf students suffered medium levels of burnout. 2- There is a strong statistically difference between the medians of the special education teachers answers on the the Maslache scale in the variant of Academic level. And the teachers with a lower academic level (Bachelor) scored higher in the Maslache burnout scale as well as suffering from greater levels of burnout. 3-There is a strong statistically difference between the medians of the special education teachers answers on the Maslache scale in the variant Years of experience. And the teachers with lowest number of years of experience scored higher in the Maslache scale as well as suffering from greater levels of burnout.